2001
DOI: 10.1046/j.1462-2920.2001.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic degradation of aromatic compounds coupled to Fe(III) reduction by Ferroglobus placidus

Abstract: Aromatic compounds are an important component of the organic matter in some of the anaerobic environments that hyperthermophilic microorganisms inhabit, but the potential for hyperthermophilic microorganisms to metabolize aromatic compounds has not been described previously. In this study, aromatic metabolism was investigated in the hyperthermophile Ferroglobus placidus. F. placidus grew at 85 degrees C in anaerobic medium with a variety of aromatic compounds as the sole electron donor and poorly crystalline F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 56 publications
0
51
0
2
Order By: Relevance
“…1). It was previously reported that F. placidus could not grow on benzene (58). The success in growing F. placidus on benzene in the studies reported here may be attributed to slight changes in the medium composition and/or the initial culturing of F. placidus in the presence of hydrogen and benzene, with hydrogen potentially providing energy to permit adaptation for growth on benzene.…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…1). It was previously reported that F. placidus could not grow on benzene (58). The success in growing F. placidus on benzene in the studies reported here may be attributed to slight changes in the medium composition and/or the initial culturing of F. placidus in the presence of hydrogen and benzene, with hydrogen potentially providing energy to permit adaptation for growth on benzene.…”
Section: Resultsmentioning
confidence: 45%
“…However, it was previously demonstrated that the hyperthermophilic archaeon Ferroglobus placidus is able to anaerobically oxidize benzoate and phenol with Fe(III) as the electron acceptor (30,58). The F. placidus genes for benzoate and phenol metabolism are homologous to those found in mesophilic bacteria, many of the genes are arranged in clusters similar to those found in bacteria, and the expression of the appropriate genes is specifically increased during growth on benzoate or phenol (30).…”
mentioning
confidence: 99%
“…Ferroglobus placidus medium was prepared as previously described (27). After autoclaving, FeCl 2 (1.3 mM), Na 2 SeO 4 (30 g/liter), Na 2 WO 4 (40 g/liter), APM salts (1 g/liter MgCl 2 , 0.23 g/liter CaCl 2 ) (28), DL vitamins (29), and all electron donors were added to the sterilized medium from anaerobic stock solutions.…”
Section: Methodsmentioning
confidence: 99%
“…Only one other thermophilic Fe(III) reducer, D. thermophilus, has this type of metabolism. The ability to use acetate is an important physiological factor for competing in anaerobic environments, since acetate is a key intermediate in the anaerobic degradation of organic matter in sedimentary environments (28,55,56). Most previously described thermophilic Fe(III) reducers do not use acetate and only incompletely oxidize other multicarbon organic acid substrates to acetate (27).…”
Section: Discussionmentioning
confidence: 99%
“…Novel hyperthermophiles with Fe(III) serving as the electron acceptor have been isolated (19,21), and it has been shown that the metabolic potential of some previously described hyperthermophiles is significantly enhanced when Fe(III) is provided as an electron acceptor (56,57). Studies with Fe(III)-reducing hyperthermophiles have documented for the first time the potential for the oxidation of important organic compounds, such as acetate, long-chain fatty acids, and aromatic compounds, in environments hotter than 80°C (21,55,56).…”
mentioning
confidence: 99%